Machine Vision Applications of Image Processing in Agriculture: A Survey - Nagarathinam, Senthil; Ravi, Thendral; Ambalavanan, Suhasini (International Journal of Computer Sciences and Engineering, 2014)
Image processing has been proved to be an effective tool for analysis in various fields and applications. Agriculture sector where the parameters like canopy, yield, quality of the product were the important measures from the farmersï¿½ point of view. This paper intends to focus on the survey of application of image processing in agriculture field such as imaging techniques, yield mapping, robotic harvesting, fruit grading, weed detection, and leaves disease detection.